Need for Closure and Political Orientation Among German University Students - Kemmelmeier, Markus (The Journal of social psychology, 1997)
Tests competing hypotheses about the relationship between general political orientation and differences in cognitive functioning. Finds that a direct relationship between right-wing orientation and closed cognitive constructs best fits the data. Notes that these findings contradict other recent studies that support a curvilinear relationship between political extremism and cognitive styles. (DSK)